2017
DOI: 10.21475/ajcs.2017.11.01.289
|View full text |Cite
|
Sign up to set email alerts
|

Identifying superior spring wheat genotypes through diallel approaches

Abstract: Diallel crosses enable plant breeders taking decisions concerning the parental choice for developing new varieties. Recently, a large number of methodological models have been reported. The objective of this study was to investigate the relationship between different methods of diallel analysis and their associations with grain yield performance in wheat (Triticum aestivum L.) segregating populations. In this study, four methods of diallel analysis were used to estimate the general (GCA) and specific (SCA) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
4
0
3
Order By: Relevance
“…This indicates that the identified characters within these components show major impacts on phenotypic genotypes. These results were consistent with previous data reported by [39,40]. Principal component analysis showed that PC1 and PC2 were governed by yield related traits, viz., PL, FLAn, CHLC, DH, PH, PW, PE, and 1000-GW.…”
Section: Correlation and Heterosis Analysissupporting
confidence: 92%
“…This indicates that the identified characters within these components show major impacts on phenotypic genotypes. These results were consistent with previous data reported by [39,40]. Principal component analysis showed that PC1 and PC2 were governed by yield related traits, viz., PL, FLAn, CHLC, DH, PH, PW, PE, and 1000-GW.…”
Section: Correlation and Heterosis Analysissupporting
confidence: 92%
“…The best linear unbiased predictor (BLUP) method, which uses components of variances estimated via restricted maximum likelihood (REML), has allowed breeders to more efficiently and accurately select and predict genetic values as it generates robust estimates. The efficiency of using mixed models in wheat breeding programs has been evaluated by Pimentel et al (2014) and Pagliosa et al (2017). Genetic diversity studies are important in wheat breeding programs because the selection of more divergent parents for crossing results in greater variability in the segregating population and, consequently, the greater is the probability of the alleles regrouping in favorable combinations.…”
Section: Cr Casagrande Et Almentioning
confidence: 99%
“…According to Pagliosa (2017), the application restricted maximum likelihood/best linear unbiased prediction (REML/BLUP) is a prominent method in parental selection. Although widespread in animal breeding and perennial species, the restricted maximum likelihood (REML) and best invariant linear predictor methods (BLUP), proposed by Patterson and Thompson (1971), are still rarely used in the improvement of annual plants and for the potential for genetic progress.…”
Section: Introductionmentioning
confidence: 99%